GOVERNMENTAL AND INSTITUTIONAL INITIATIVES AND ACTIONS FOR THE ATTRACTION AND EXPANSION OF E-COMMERCE BY WOMEN IN BANGLADESH - Mimi, Afsana; Imran, Md. Ali; Beg, Tahrima Haque; Rahman, Md. Sazidur (American Economic & Social Review, 2022)
This research investigates the initiatives and actions taken by the Government of Bangladesh and institutions to attract women into e-commerce and introduce these women as financially independent. The existence and power of women in Bangladesh are very weak, and this is due to dependency, lack of education, and skills. To remove these obstacles and empower women through e-commerce, the Government and different institutions are taking various initiatives and actions as they can contribute to the development of Bangladesh. This study evaluates how Government and other institutions are working to introduce e-commerce as a strong tool for women’s economic independence in Bangladesh. The Government is taking action to provide direct funds, introducing simple policies, tax exemptions, easy business space, transportation assistance, and many other ways. Different organizations are also working to assist the Government of Bangladesh in empowering women through e-commerce. The policy recommendations could be helpful for The Government of the People’s Republic of Bangladesh to mitigate its challenges and make this sector more profitable.